2023
DOI: 10.1093/plphys/kiad295
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution genome mapping and functional dissection of chlorogenic acid production in Lonicera maackii

Abstract: Amur honeysuckle (Lonicera maackii) is a widely used medicinal plant of the Caprifoliaceae family that produces chlorogenic acid. Research on this plant mainly focuses on its ornamental value and medicinal compounds, but a reference genome sequence and molecular resources for accelerated breeding are currently lacking. Herein, Nanopore sequencing and high-throughput chromosome conformation capture (Hi-C) allowed a chromosome-level genome assembly of Lonicera maackii (2n = 18). A global view of the gene regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…The subcellular localization analysis showed that the CtHCT-eGFP fusion gene produced significant green fluorescent signals in both the cytosol and nucleus of N. benthamiana (Figure 6E), in agreement with previous studies that have reported the cytoplasm as the main site of CGA biosynthesis [16]. Subsequently, transient overexpression of the CtHCT-eGFP fusion gene in N. benthamiana indicated a 41.56% increase in the relative CGAs (namely 5-caffeoyl quinic acid) content (Figure 6F,G).…”
Section: Analysis Of Bioinformatics Subcellular Localization and Tran...supporting
confidence: 91%
See 2 more Smart Citations
“…The subcellular localization analysis showed that the CtHCT-eGFP fusion gene produced significant green fluorescent signals in both the cytosol and nucleus of N. benthamiana (Figure 6E), in agreement with previous studies that have reported the cytoplasm as the main site of CGA biosynthesis [16]. Subsequently, transient overexpression of the CtHCT-eGFP fusion gene in N. benthamiana indicated a 41.56% increase in the relative CGAs (namely 5-caffeoyl quinic acid) content (Figure 6F,G).…”
Section: Analysis Of Bioinformatics Subcellular Localization and Tran...supporting
confidence: 91%
“…The fusion construct was introduced into Agrobacterium tumefaciens GV3101 using the freeze-thaw method. Positive clones with kanamycin resistance were validated with PCR ( Table S2 ) and used for transient transformation in Nicotiana benthamiana ( N. benthamiana ) following previously reported methods [ 16 ]. On day 3 after transformation, the fluorescence signals of N. benthamiana in the experimental (35S:: CtHCT-eGFP ) and control groups (35S:: eGFP ) were observed under a confocal microscope (LSM 980, Carl Zeiss AG, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…scitamineum have been investigated by high-throughput sequencing, , but most of them focused mainly on the exploration of single genes or pathways, and relatively few studies were conducted on the regulatory relationships between TFs and various response mechanisms. In recent years, the TO-GCN, an effective way to elaborate gene regulatory networks, has been widely used in various plants. Li et al applied the TO-GCN to analyze the gene regulatory networks of amur honeysuckle (Lonicera maackii) and revealed that the chlorogenic acid biosynthesis and anthocyanin metabolism pathways were responsible for the accumulation of red pigments. Zhao et al used time-course transcriptomics analysis and constructed multiple subnetworks to explore the poplar response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the TO-GCN, an effective way to elaborate gene regulatory networks, has been widely used in various plants. 15−17 Li et al 42 applied the TO-GCN to analyze the gene regulatory networks of amur honeysuckle (Lonicera maackii) and revealed that the chlorogenic acid biosynthesis and anthocyanin metabolism pathways were responsible for the accumulation of red pigments. Zhao et al 16 used timecourse transcriptomics analysis and constructed multiple subnetworks to explore the poplar response to salt stress.…”
Section: To-gcns Of Sugarcane Under S Scitamineum Stressmentioning
confidence: 99%